Georgia Architectural and Historic Properties Survey of Rural [287] 10 miles south of Quitman on Hwy. 221, Valdosta, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural [287] 10 miles south of Quitman on Hwy. 221, Valdosta, Ga. December 1980. 1 story rectangular clapboard house with gabled roof. Square posts support hipped porch. Double hung sash windows with 6/6 lights are shuttered. Transom and sidelights. Interior chimney. Set on brick piers. Long oak lined drive leads right to the house. Good condition. Date of Construction: Between 1855 & 1867. Built on hand hewn logs put together with wooden pegs. Center section is the original building. One of 3 houses built in the Hickory Head community by the McMullen family. Significant architecturally because of the method and materials of construction as well as age.
Georgia Architectural and Historic Properties Survey of Rural [287] 10 miles south of Quitman on Hwy. 221, Valdosta, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 1.68 MB (1,769,329 bytes).
Keywords: Valdosta (Ga.); Historic buildings; Real property surveys; Brooks County (Ga.); Lowndes County Historical Society (Lowndes County, Ga.)